Tryptophan metabolism in Klebsiella aerogenes: regulation of the utilization of aromatic amino acids as sources of nitrogen. - Paris, C G (1981)
Klebsiella aerogenes utilized aromatic amino acids as sole sources of nitrogen but not as sole sources of carbon. K. aerogenes abstracted the alpha-amino group of these compounds by transamination and excreted the arylpyruvate portions into the medium. When tryptophan was utilized as the sole source of nitrogen by K. aerogenes, indolepyruvate was excreted into the medium, where it polymerized non-enzymatically to form a brick red pigment. At least four separate aromatic aminotransferase activities were found in K. aerogenes. One activity (aromatic aminotransferase I) appeared to be solely responsible for the aminotransferase reaction necessary for the growth of K. aerogenes when tryptophan was the source of nitrogen; the loss of this activity by mutation (tut) prevented the growth of cells on media containing this and other aromatic amino acids. None of the other aminotransferase activities in the cells could substitute for aromatic aminotransferase in this regard. Tryptophan-dependent pigment formation in K. aerogenes was positively controlled by the intracellular level of glutamine synthetase. Nevertheless, the aromatic aminotransferase activity in cells varied less than 2-fold in response to 10-fold or greater changes in the levels of glutamine synthetase. Glutamine synthetase affected the ability of the cells to take up tryptophan from the medium.